Letter commenting on survival after short-or long-term ventilation after acute spinal cord injury: A single-centre 25-year retrospective study. - Hutton, J.L.; Watt, J.H.W.; Wiredu, E. (My University, 2012)
No Abstract
Keywords: EMTREE medical terms: assisted ventilation; comorbidity; groups by age; human; letter; life expectancy; long term care; mortality; priority journal; retrospective study; spinal cord injury; survival rate